THE EFFECT OF MSME PRODUCT MARKETING ABILITY AND INNOVATION ON COMPETITIVE ADVANTAGE DURING THE COVID-19 PANDEMIC - Sutrisno Sutrisno (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The goal of this research is to analyze and calculate the impact of marketability and product innovation variables on competitive advantage. The researchers took a quantitative approach, employing narrative and associative methods. The population in this study was Tegal city banana chip/lanntak SMEs, with a total sample of 31 Tegal banana/lanntak chip SMEs with specified criteria, non-probabilistic or using saturated sampling techniques. The analytical method used is multiple correlation analysis, multiple regression analysis, the certainty test, and partial hypothesis testing (t-test) combined with the F-test. Based on the t-test results, the'marketability' variable has a significant positive effect on the 'competitive advantage' variable, while the 'product innovation' variable has a significant negative effect on the 'competitive advantage' variable. show.